Safety and Efficacy of Chemotherapy Combined with Anlotinib Plus Anlotinib Maintenance in Chinese Patients with Advanced/Metastatic Soft Tissue Sarcoma - Wang H (OncoTargets and Therapy, 2020)
Hai-ying Wang, Jun-feng Chu, Peng Zhang, Jia-qiang Wang, Zheng Yan, Shu-na Yao, Zhi-hua Yao, Yan-yan Liu Department of Internal Medicine, Affiliated Cancer Hospital of Zhengzhou University, Henan Cancer Hospital, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Zhi-hua Yao; Hai-ying WangDepartment of Internal Medicine, Affiliated Cancer Hospital of Zhengzhou University, Henan Cancer Hospital, No. 127 Dongming Road, Zhengzhou, Henan 450008, People’s Republic of ChinaTel/Fax +86 371-65587791; +86 13838326280Email happierzhihua@126.com; 470242877@qq.comPurpose: Anlotinib, a newly developed oral small-molecule receptor tyrosine kinase inhibitor (TKI), has been shown to have encouraging activity against sarcoma. The purpose of this study was to retrospectively evaluate the safety and clinical efficacy of chemotherapy combined with anlotinib plus anlotinib maintenance in advanced/metastatic soft tissue sarcoma (STS) patients in a real-world setting in China.Patients and Methods: We retrospectively collected the medical data of thirty-two patients with advanced/metastatic STS who received chemotherapy combined with anlotinib plus anlotinib maintenance therapy. The objective response rate (ORR) and disease control rate (DCR) were calculated according to the RECIST 1.1 criteria. The progression-free rates (PFRs) at three and six months, the progression-free survival (PFS) time, and adverse events were recorded.Results: On the basis of investigator assessments, two patients (6%) achieved CR (complete response) and nine patients (28%) achieved PR (partial response), with an ORR of 34%. Eleven patients (34%) achieved SD (stable disease), and ten patients (31%) achieved PD (progression disease), with a DCR of 69%. The progression-free rates (PFRs) at three and six months were 81% and 69%, respectively. The median PFS time was 8.2 months. The hematologic and non-hematologic toxicities were manageable. The most common grade 3 and 4 adverse events were febrile neutropenia (9%), leukopenia (19%), thrombocytopenia (3%), anemia (6%), anorexia (6%), vomiting (3%), and hypertension (6%). The combination therapy was generally well tolerated.Conclusion: Our study suggests that chemotherapy combined with anlotinib plus anlotinib maintenance therapy had good efficacy and resulted in more favorable survival with good tolerance among patients with advanced/metastatic STS.Keywords: advanced/metastatic soft tissue sarcoma, anlotinib, chemotherapy, toxicity